1989
DOI: 10.1364/ao.28.001919
|View full text |Cite
|
Sign up to set email alerts
|

Efficient algorithm for designing a ternary valued filter yielding maximum signal to noise ratio

Abstract: An efficient algorithm for designing a ternary valued filter yielding the highest signal to noise ratio (SNR) is utlined. Numerical evaluations using the image of a tank indicate that using such a filter can provide an improvement in SNR of ~5 dB over the conventional binary phase-only filter (BPOF). This is superior to the 1-dB improvement obtained for that image by varying the threshold line angle (TLA) in filter binarization. Simulation results are presented. They agree with the numerically computed SNRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…The POFs and BPOFs as introduced originally are allpass, i.e., these filters have unit magnitude at all frequencies. Recently, it has been shown that the noise tolerance 8 , 9 and correlation peak sharpiness 1 0 of these filters can be maximized by setting some frequencies to have zero magnitude. The set of frequencies for which the filter magnitude is nonzero is known as the Region of Support (ROS).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The POFs and BPOFs as introduced originally are allpass, i.e., these filters have unit magnitude at all frequencies. Recently, it has been shown that the noise tolerance 8 , 9 and correlation peak sharpiness 1 0 of these filters can be maximized by setting some frequencies to have zero magnitude. The set of frequencies for which the filter magnitude is nonzero is known as the Region of Support (ROS).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…With the help Eq. (9). To prove that this is true, let us assume that the filters of simulation examples, we have shown that for the particular result in angle 13i * 15* when we use Eq.…”
Section: Ic1 = Jh(f)s(f)exp(-0)dfmentioning
confidence: 87%
See 3 more Smart Citations